Low Prevalence of Leptospira Carriage in Rodents in Leptospirosis-Endemic Northeastern Thailand - Krairojananan, Panadda (Trop Med Infect Dis, 2020)
Leptospirosis is a neglected zoonotic disease affecting mostly the world’s tropical regions. The rural people of northeastern Thailand suffer from a large number of leptospirosis infections, and their abundant rice fields are optimal rodent habitats. To evaluate the contribution of diversity and carriage rate of pathogenic Leptospira in rodent reservoirs to leptospirosis incidence, we surveyed rodents, between 2011 and 2012, in four provinces in northeastern Thailand with the highest incidence rates of human leptospirosis cases. We used lipL32 real-time PCR to detect pathogenic Leptospira in rodent kidneys, partial 16S rRNA gene sequencing to classify the infecting Leptospira species, and whole 16S rDNA sequencing to classify species of isolated Leptospira. Overall prevalence of Leptospira infection was 3.6% (18/495). Among infected rodents, Bandicota indica (14.3%), Rattus exulans (3.6%), and R. rattus (3.2%) had renal carriage. We identified two pathogenic Leptospira species: L. interrogans (n = 15) and L. borgpetersenii (n = 3). In addition, an L. wolffii (LS0914U) isolate was recovered from the urine of B. indica. Leptospira infection was more prevalent in low density rodent populations, such as B. indica. In contrast, there was a lower prevalence of Leptospira infection in high density rodent populations of R. exulans and R. rattus.